2021
DOI: 10.1177/00178969211026345
|View full text |Cite
|
Sign up to set email alerts
|

Using fitness trackers to increase physical activity in a US Army health initiative

Abstract: Objective: Fitness trackers are appealing in public health intervention programmes aimed at promoting physical activity, but it is unclear whether tracker use leads to health behaviour change in soldiers. This programme evaluation investigated the effects of fitness tracker usage on goal-setting, self-monitoring and physical activity behaviours in soldiers participating in a 6-month pilot health promotion programme focused on improving sleep, activity and nutrition behaviours. Design: Participants in this prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Fitness is so highly valued that it is unsurprising these findings show no difference in reported exercise and self-reported physical and mental wellness. Although there appears to be a great deal of interest in replacing existing physical fitness regimens and evaluations 2,22 or optimizing performance for operational advantage, 23,24 the influence of wearable fitness trackers may be of dubious utility without further technological maturation and systems integration. 25 We found that, overall, 9.3% of respondents demonstrated inadequate health literacy based on the SILS.…”
Section: Discussionmentioning
confidence: 99%
“…Fitness is so highly valued that it is unsurprising these findings show no difference in reported exercise and self-reported physical and mental wellness. Although there appears to be a great deal of interest in replacing existing physical fitness regimens and evaluations 2,22 or optimizing performance for operational advantage, 23,24 the influence of wearable fitness trackers may be of dubious utility without further technological maturation and systems integration. 25 We found that, overall, 9.3% of respondents demonstrated inadequate health literacy based on the SILS.…”
Section: Discussionmentioning
confidence: 99%
“…Soldiers in the P3 Pilot also participated in group challenges to support healthy behaviors. In addition to the P3 educational curriculum, some Soldiers received a personal fitness tracker as an additional intervention (see also Brown et al, 2021). Participating Soldiers were assigned to one of three conditions: a condition that received the educational material and curriculum only, one that received the educational material, curriculum, and a fitness tracker, and a comparison condition that received neither curriculum nor a fitness tracker.…”
Section: Introductionmentioning
confidence: 99%